Kedudukan dan Perlindungan Hukum terhadap Bendesa Adat sebagai Subjek dalam Operasi Tangkap Tangan - Cahyani, Putu Rita; Antari, Putu Eva Ditayani; Darma, I Made Wirya; Gorda, AAA Ngurah Tini Rusmini (Legalita, 2025)
This study analyzes the position and legal protection of the Bendesa Adat as a subject in a Sting Operation (OTT). As the highest leader in Balinese traditional villages, the Bendesa Adat holds strategic roles in administration, resource management, and traditional ceremonies. Despite this authority, the Bendesa Adat remains bound by national law and may become the subject of law enforcement in cases of suspected abuse of power or criminal acts. The research employs a normative juridical method with a qualitative descriptive approach, using primary legal sources such as Law No. 6 of 2014 on Villages, the Criminal Procedure Code, laws governing the Corruption Eradication Commission, the Police, the Attorney General, regional regulations on traditional villages, and relevant legal literature. The analysis focuses on three aspects: the Bendesa Adat’s legal position, the OTT mechanism, and the protection of human rights. Findings show the Bendesa Adat has a dual position as a strategic traditional leader and a legal subject under national regulations. While OTT is an effective enforcement mechanism, it must respect socio-cultural norms to preserve community stability. Legal safeguards, including the right to counsel and due process, are essential to balance law enforcement with respect for customary law